Inkoherensi Sistemik dalam Pembiayaan Pendidikan Vokasi Berbasis Kemitraan pada Teaching Factory Perikanan dan Kelautan - Dani Darmawan; Dedy Achmad Kurniady; Taufani Chusnul Kurniatun; Aan Komariah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: This study aims to analyze systemic incoherence in partnership-based vocational education financing for fisheries and marine Teaching Factories. The study was conducted using a qualitative case study design to understand how financing mechanisms, industry partnerships, production-based learning, governance practices, and institutional arrangements interact within a real vocational education setting. Data were collected through semi-structured interviews, field observations, document analysis, and stakeholder confirmation involving school leaders, finance officers, productive teachers, Teaching Factory managers, and industry partners. The findings show that the Teaching Factory was supported by multiple financing sources, industry collaboration, and real production-based learning through vaname shrimp farming. However, these components had not yet formed a fully coherent and integrated financing system. Five main forms of systemic incoherence were identified: misalignment between policy direction and production needs, administrative financing and productive financing, industry partnership and learning design, formal planning and field dynamics, and formal governance and adaptive coordination. The study concludes that the main challenge in partnership-based vocational education financing is not merely funding adequacy or the existence of industry partnership, but the weak integration among financing, production, partnership, governance, and learning. Therefore, vocational schools and policymakers should develop an integrated financing governance model that connects accountability with operational flexibility, institutionalises industry partnership, supports production risk management, and strengthens the sustainability of production-based vocational education. Keywords: Fisheries and marine Teaching Factory; Industry partnership; Production-based learning; Systemic incoherence; Vocational education financing. Abstrak: Penelitian ini bertujuan menganalisis inkoherensi sistemik dalam pembiayaan pendidikan vokasi berbasis kemitraan pada Teaching Factory sektor perikanan dan kelautan. Penelitian ini menggunakan desain studi kasus kualitatif untuk memahami interaksi antara mekanisme pembiayaan, kemitraan industri, pembelajaran berbasis produksi, tata kelola sekolah, dan pengaturan kelembagaan dalam konteks pendidikan vokasi nyata. Data dikumpulkan melalui wawancara semi-terstruktur, observasi lapangan, analisis dokumen, dan konfirmasi pemangku kepentingan yang melibatkan pimpinan sekolah, pengelola keuangan, guru produktif, pengelola Teaching Factory, serta mitra industri. Hasil penelitian menunjukkan bahwa Teaching Factory didukung oleh berbagai sumber pembiayaan, kolaborasi industri, dan pembelajaran berbasis produksi nyata melalui budidaya udang vaname. Namun, berbagai komponen tersebut belum membentuk sistem pembiayaan yang sepenuhnya koheren dan terintegrasi. Lima bentuk utama inkoherensi sistemik ditemukan, yaitu ketidaksesuaian antara arah kebijakan dan kebutuhan produksi, pembiayaan administratif dan pembiayaan produktif, kemitraan industri dan desain pembelajaran, perencanaan formal dan dinamika lapangan, serta tata kelola formal dan koordinasi adaptif. Penelitian ini menyimpulkan bahwa tantangan utama bukan semata-mata kecukupan dana atau keberadaan kemitraan industri, melainkan lemahnya integrasi antara pembiayaan, produksi, kemitraan, tata kelola, dan pembelajaran. Oleh karena itu, sekolah vokasi dan pembuat kebijakan perlu mengembangkan model tata kelola pembiayaan terintegrasi yang menghubungkan akuntabilitas dengan fleksibilitas operasional, melembagakan kemitraan industri, mendukung manajemen risiko produksi, dan memperkuat keberlanjutan pendidikan vokasi berbasis produksi. Kata kunci: Inkoherensi sistemik; Kemitraan industri; Pembelajaran berbasis produksi; Pembiayaan pendidikan vokasi; Teaching Factory perikanan dan kelautan.